Basidiomata induction and characterization of ganoderrna from oil palm (Elaeis guineensis) on three agrowaste substrates - Abdullah, Faridah (Universiti Putra Malaysia Press, 1996)
Ganoderma is a causal pathogen ofbasal stem rot ofoil palm. Members ofthis genus are very diverse in the tropics but the significance ofthis diversity is difficult to relate to taxonomic levels in the genus, largely because of the lack of knowledge about the stability ofparticular features of the fungus. This paper outlines a culture method that induces the formation of Ganoderma basidiomata under controlled conditions, and thus enables the stability of characters to be evaluated. Using induced basidiomata, selected characteristics were found to be reproducible on 3 solid substrates, palm press fibres (PPF), cotton fibres (CF) and rubberwood sawdust (RSD). The rate of mycelial colonization varied significantly with different substrates but, once formed, the rates of basidioma growth and development were comparable irrespective ofsubstrate type. Besides the growth rates ofGanoderma, this study also offers insight into the status of colour in mature basidioma, the potential of stipe attachment as a taxonomic character, and the requirement for high ambient RH values for spore production of induced basidiomata.